Device Characteristics of CZTSSe Thin‐Film Solar Cells with 12.6% Efficiency. Issue 7 (27th November 2013) - Wang, Wei; Winkler, Mark T.; Gunawan, Oki; Gokmen, Tayfun; Todorov, Teodor K.; Zhu, Yu; Mitzi, David B.
<x xml:space="preserve">Abstract</x> A 12.6% Cu2ZnSnSxSe4–x (CZTSSe) solar cell is presented with detailed device characteristics. Both short‐circuit current density (Jsc) and open circuit voltage (Voc) increase in the 12.6% champion, relative to previous devices, due to better bulk CZTSSe quality and improved optical architecture. The reduction in Voc deficit shows opportunities to push CZTSSe solar cells to higher efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>